Colonial policies and the failure of Somali secessionism in the Northern frontier district of Kenya colony, c.1890-1968 - Abdullahi, Abdirashid (Rhodes University, Faculty of Humanities, Department of History, 1998)
This thesis examines the events that took plac,e. in the Northern Frontier District I North Eastern Province of Kenya hetween the late nineteenth century and 1968. After 1900 the imposition of colonial policies impacted on the socio-economic and political structures of the Somali people. This thesis also examines the nature of Somali resistance lP- to the late 1920s when Somali society was finally pacified. It further examines colonial policies such as the creation of the Somali-Galla line in 1919, the separation of the J uhaland region from the Kenya Colony in 1926 and the Special District Ordinance of 1934. Between 1946 and 1948 the British Government through its Foreign Minister, Ernest Bevin, attempted to unify Somali territories in the Horn of Africa and this raised Somali hopes of uni fication. The Bevin Plan collapsed because of the opposition of the United States, the Soviet Union, the French and Ethiopian leaders. Similar hopes of NFD Somali unification were raised hetween 1958 and 1963 because of the unification of the former British Somali land and Italian Somaliland. Due to the imminent end of British colonial rule in Kenya, the NFD Somali leaders demanded secession from Kenya to join up with the nascent Somali republic. But the NFDSomali hopes of unification with the Somali Repuhlic were dashed by 1964 because of the same opposition provided by the United States, the French and the Ethiopians. The British Government were all along half-hearted towards Somali unification attempts even though the field administrators adopted a pro-Somali attitude to the issue. In the early 1960s, however, the NFD Somali leaders were faced with the additional opposition of the new KANU government in Kenya. In 1964 the failure of the NFD Somalis to secede from Kenya led to the guerrilla war, what the Kenyan government called the 'shifta movement', that engulfed the North Eastern Region until 1968 when the Arusha Memorandum of Understanding was signed between the Kenyan and the Somali Governments. The signing of the Arusha Memorandum of Understanding by the Kenyan and Somali Governments did not satisfyÂ· the NFD Somalis hopes of joining the Somali Republic. The main conclusion of this thesis is that the N FD Somalis, except for few collahorators, did at no time, whether in the colonial or post-colonial eras, accept heing in Kenya. By the late 1960s the prospects of NFD Somalis unifying with the Somali Republic were, in view of the forces arrayed against the Somali secessionist movement, slim; and they have remained slim since then.
Keywords: Somalis -- Kenya -- History; Kenya -- History -- 1963-; Kenya -- Politics and government; Decolonization -- Kenya -- History -- 20th century; Kenya -- History -- To 1963